Tailoring terahertz plasmons with silver nanorod arrays - Cao, Wei (Nature Publishing Group, 2013)
Plasmonic materials that strongly interact with light are ideal candidates for designing subwavelength photonic devices. We report on direct coupling of terahertz waves in metallic nanorods by observing the resonant transmission of surface plasmon polariton waves through lithographically patterned films of silver nanorod (100 nm in diameter) micro-hole arrays. The best enhancement in surface plasmon resonant transmission is obtained when the nanorods are perfectly aligned with the electric field direction of the linearly polarized terahertz wave. This unique polarization-dependent propagation of surface plasmons in structures fabricated from nanorod films offers promising device applications. We conclude that the anisotropy of nanoscale metallic rod arrays imparts a material anisotropy relevant at the microscale that may be utilized for the fabrication of plasmonic and metamaterial based devices for operation at terahertz frequencies.